Environment: protecting natural resources and the balance of biodiversity for the Southern District of Iraq - اسماعيل رضا, عادل (Al-Adab Journal, 2018)
On the subject of biodiversity is relatively recent, the term appeared in 1968, and several levels was including ecosystem diversity, which means the center where you live organisms and the addition reactions of physical, biological and chemical evidence and between organisms and peppered the transmission of matter and energy to and from the center . However, the exploitation of human and natural resources for wildly wrong led to damage to the environment and the disruption of equilibrium became so weak fragile is unable to meet its requirements after it was genes store for the emergence of the species, and a source of food, medicine, mainly Alaaklogih systems. Perhaps the best proof of that is what happened for the Southern District of Iraq from changing environmental and natural system, the effect of exposure structure of its resources to the deterioration of the military motives, and to exploit its potential in non-thoughtful leading to the loss and the decline of biodiversity for many live its objects in terrestrial and aquatic environments and became the ecosystem and agricultural production systems plant and animal is able to balance the ecosystem that survival depends on biodiversity sources of components, the more the bigger the diversity led to an increased genetic resources important to the environment and sustainability.